2011
DOI: 10.3389/fendo.2011.00076
|View full text |Cite
|
Sign up to set email alerts
|

Landmarks in Insulin Research

Abstract: Ever since the discovery of insulin and its role in the regulation of glucose uptake and utilization, there has been great interest in insulin, its structure and the way in which it interacts with its receptor and effects signal transduction. As the 90th anniversary of the discovery of insulin approaches, it is timely to provide an overview of the landmark discoveries relating to the structure and function of this remarkable molecule and its receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 101 publications
(122 reference statements)
0
31
0
1
Order By: Relevance
“…Each monomer in the receptor homo‐dimer is comprised of two leucine‐rich domains (L1 and L2) separated by a cysteine‐rich (CR) domain and followed by three fibronectin type‐III repeats, F1, F2, and F3, which is connected via a single transmembrane helix to the intracellular kinase domain 6. Although the molecular details of insulin binding and receptor activation remain elusive, partly due to the lack of structure of the hormone‐bound receptor, the crystal structure of apo‐IR (IR $\Delta \beta$ 7; PDB code 2DTG) has provided structural bases for domain organization in the IR homodimer,8–13 where subunits are arranged in a “folded‐over inverted V” conformation with each of the two insulin‐binding pockets formed by the (L1–CR–L2) motif of one subunit and the (F1–F2–F3) motif of the other subunit. A homology model of the IGF1R ectodomain validated by small‐angle X‐ray scattering (SAXS) data displays similar overall architecture 14…”
Section: Introductionmentioning
confidence: 99%
“…Each monomer in the receptor homo‐dimer is comprised of two leucine‐rich domains (L1 and L2) separated by a cysteine‐rich (CR) domain and followed by three fibronectin type‐III repeats, F1, F2, and F3, which is connected via a single transmembrane helix to the intracellular kinase domain 6. Although the molecular details of insulin binding and receptor activation remain elusive, partly due to the lack of structure of the hormone‐bound receptor, the crystal structure of apo‐IR (IR $\Delta \beta$ 7; PDB code 2DTG) has provided structural bases for domain organization in the IR homodimer,8–13 where subunits are arranged in a “folded‐over inverted V” conformation with each of the two insulin‐binding pockets formed by the (L1–CR–L2) motif of one subunit and the (F1–F2–F3) motif of the other subunit. A homology model of the IGF1R ectodomain validated by small‐angle X‐ray scattering (SAXS) data displays similar overall architecture 14…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the 3 insulin disulfides and the aromatic amino acids (B24, B25, and A19) in insulin function are well-established (Murray-Rust et al, 1992). Mutagenesis data indicated that a second receptor-binding surface is present on insulin that involves residues A12 (S), A13 (L), A17 (E), B10 (H), B13 (D), and B17 (L) (Ward and Lawrence, 2011). Multiple alignment analyses showed that the amino acid sequence of the B-chain of Alligator sinensis and birds differed at some sites, such as B13, B21, and B30.…”
Section: Discussionmentioning
confidence: 99%
“…показали, что ИР представляет собой тетрамер, образованный двумя α-и двумя β-субъединицами, соединенными ди-сульфидными мостиками (см. рисунок) [13]. ИР от-носится к трансмембранным гликопротеинам, α-субъ-еди ницы которого находятся во внеклеточной обла-сти и отвечают за связывание инсулина, а β-субъ-единицы образуют внутриклеточный домен, цито-плазматическая область которого содержит тиро-зинкиназный домен, с помощью которого фосфо-рилируются внутриклеточные белки-субстраты ин-сулинового сигнального пути по специфическим аминокислотным остаткам тирозина [14].…”
Section: строение инсулинового рецептораunclassified